(untitled) (Research, Society and Development, 2021)
The objective of this research was to evaluate the effectiveness of the didactic game as a facilitator in the teaching-learning process. For this purpose, a qualitative research strategy of exploratory nature was used, through a field research carried out with 9 students, trainees of the Nursing Technician course in a public institution, data collection was carried out through the application of a didactic game, after the game, students answered a questionnaire with questions that characterized the participants and evaluated the effectiveness of the game. The analysis of the instruments revealed that the game was well accepted, being an important tool for the development of the activity and, consequently, for the construction of knowledge. It is concluded that the awareness of teachers about the importance of educational games is possible by encouraging the practice of this methodology as a facilitator of teaching and learning.